Analisis Tingkat Kepuasan Konsumen Pada Toko Sembako Rizka Di Tenggarong - Susilawati, Dewi; Wijayanti, Silvana; Wijayanti, Akhmadiansyah (I-Con Media, 2025)
Consumer satisfaction is the main priority in this research because the level of competition is increasingly fierce among grocery stores. One way to create consumer satisfaction in grocery stores is to improve product quality and pricing strategies. If the grocery store provides good quality products and sets appropriate prices, consumers will feel satisfied. With a feeling of satisfaction, consumers will come back to the grocery store. The aim of this research is to determine the influence of product quality and price variables on consumer satisfaction at the Rizka grocery store in Tenggarong, both simultaneously and partially. The sample used in this research was 78 people and the analytical tool used for this research was multiple linear regression using SPSS 26 software. Based on the research results, it shows that (1) Product Quality and Price have a significant effect simultaneously on Consumer Satisfaction, (2) Product Quality has no significant effect on Consumer Satisfaction, (3) Price has a significant effect on Consumer Satisfaction. Keywords: Product Quality, Price, Consumer Satisfaction